Factores relacionados a la sobrecarga de cuidadores familiares en tiempos de pandemia COVID-19 de la ciudad de Iquitos año 2022 - Moncada Yaicate, Miguel Angel (2024)
The objective of the research was to define the relationship between sociodemographic and comorbidity factors with the overload of family caregivers of older adults in times of the COVID-19 pandemic in the city of Iquitos 2022. The study was descriptive with a non-experimental, correlational and cross-sectional design. The population was 2,761 caregivers and the sample was 337. The instruments used were the sociodemographic and comorbidity factors questionnaire and the Zarit care burden scale. The result found was (56.7%) were under 60 years of age, with predominant participation of the female group (63.2%) with a predominance of secondary education (49.3%). A higher percentage had health insurance (96.7%). The comorbidity of family caregivers, the average time (years) they suffered from an illness was 6.2 ± 8.6, with a slight difference between female and male caregivers. 28.2% of caregivers suffered from hypertension, being more common in the female group (31.0%), 8.0% had Diabetes Mellitus, with a higher incidence in women. The level of overload of the family caregiver, 59.6% (201) reported no overload, while 40.3% (236) were evaluated with light and intense overload. comorbidity and overload, a significant relationship (p=0.031) was found between hypertension and overload. But no significant relationships were found for Diabetes Mellitus, Dyslipidemias, CKD and Asthma/COPD. It was concluded that of the sociodemographic factors studied, only age and level of education are associated with overload and only hypertension is associated with comorbidity